Effects of electromagnetic fields on bone loss in hyperthyroidism rat model. Issue 2 (14th December 2016) - Liu, Chaoxu; Zhang, Yingchi; Fu, Tao; Liu, Yang; Wei, Sheng; Yang, Yong; Zhao, Dongming; Zhao, Wenchun; Song, Mingyu; Tang, Xiangyu; Wu, Hua
Abstract : Optimal therapeutics for hyperthyroidism‐induced osteoporosis are still lacking. As a noninvasive treatment, electromagnetic fields (EMF) have been proven to be effective for treating osteoporosis in non‐hyperthyroidism conditions. We herein systematically evaluated the reduced effects of EMF on osteoporosis in a hyperthyroidism rat model. With the use of Helmholtz coils and an EMF stimulator, 15 Hz/1 mT EMF was generated. Forty‐eight 5‐month‐old male Sprague–Dawley rats were randomly divided into four different groups: control, levothyroxine treated (L‐T4), EMF exposure + levothyroxine (EMF + L‐T4), and EMF exposure without levothyroxine administration (EMF). All rats were treated with L‐T4 (100 mg/day) except those in control and EMF groups. After 12 weeks, the results obtained from bone mineral density analyses and bone mechanical measurements showed significant differences between L‐T4 and EMF + L‐T4 groups. Micro CT and bone histomorphometric analyses indicated that trabecular bone mass and architecture in distal femur and proximal tibia were augmented and restored partially in EMF + L‐T4 group. In addition, bone thyroid hormone receptors (THR) expression of hyperthyroidism rats was attenuated in EMF + L‐T4 group, compared to control group, which was not observed in L‐T4 group. According to these results, we concluded that 15 Hz/1 mT EMF significantly inhibited bone loss and micro architecture deterioration in hyperthyroidism rats, which might occur due to reduced THR expression caused by EMF exposure. Bioelectromagnetics. 38:137–150, 2017. © 2016 Wiley Periodicals, Inc.